To Move or not to Move: What Drives Residential Mobility Rates in the OECD? - Caldera Sánchez, Aida (OECD Economics Department Working Papers, 2011)
Residential mobility is closely tied to housing market forces and has important implications for labour mobility and the efficient allocation of resources across the economy. This paper analyses patterns of residential mobility across OECD countries and the role of housing policies in enhancing or hampering residential mobility. Based on cross-sectional household data for 25 countries, the results suggest that differences in residential mobility across countries are partially related to differences in public policies. After controlling for household and country-specific characteristics, residential mobility is higher in countries with lower transaction costs, more responsive housing supply, lower rent controls and tenant protection. Residential mobility tends also to be higher in environments with greater access to credit, suggesting that financial deregulation - by lowering borrowing costs and facilitating access to mortgage finance - facilitates mobility. This cross-country evidence is supported by city and state-level evidence for the United States, which also highlights the potential risks that high leverage rates pose to residential mobility